Find the best answers to your questions with the help of IDNLearn.com's expert contributors. Join our community to receive timely and reliable responses to your questions from knowledgeable professionals.
Sagot :
Answer:
-5
Step-by-step explanation:
h(x) = -3x - 2
h(x) = 1
[ just put '1' in place of every 'x' ]
-3(1) -2
= -3 -2
= -5 (answer)
Answer:
The answer is (-5)
Step-by-step explanation:
h(x) = -3x – 2; h(x) = 1
h(1) = -3(1) – 2
h(1) = -3 – 2
h(1) = -5
Thus, The answer is (-5)
-TheUnknownScientist 72
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. IDNLearn.com is committed to providing the best answers. Thank you for visiting, and see you next time for more solutions.